Experiment and Theory Clarify: Sc+ Receives One Oxygen Atom from SO2 to Form ScO+, which Proves to be a Catalyst for the Hidden Oxygen‐Exchange with SO2. Issue 5 (20th January 2022) - Mercero, Jose M.; Rezabal, Elixabete; Ugalde, Jesus M.; Weiske, Thomas; Li, Jilai
Abstract: Using Fourier‐transform ion cyclotron resonance mass spectrometry, it was experimentally determined that Sc + in the highly diluted gas phase reacts with SO2 to form ScO + and SO. By 18 O labeling, ScO + was shown to play the role of a catalyst when further reacting with SO2 in a Mars‐van Krevelen‐like (MvK) oxygen exchange process, where a solid catalyst actively reacts with the substrate but emerges apparently unchanged at the end of the cycle. High‐level quantum chemical calculations confirmed that the multi‐step process to form ScO + and SO is exoergic and that all intermediates and transition states in between are located energetically below the entrance level. The reaction starts from the triplet surface; although three spin‐crossing points with minimal energy have been identified by computational means, there is no evidence that a two‐state scenario is involved in the course of the reaction, by which the reactants could switch from the triplet to the singlet surface and back. Pivotal to the oxygen exchange reaction of ScO + with SO2 is the occurrence of a highly symmetric four‐membered cyclic intermediate by which two oxygen atoms become equivalent. Abstract : Sc + is oxidized by SO2 to ScO +, which catalyzes the hidden oxygen exchange reaction with SO2 in a Mars‐van Krevelen‐like reaction.